Factors Affecting Decisions on Imports of Goods on E-Commerce Platforms - Hanh, Vu Thi; Thai, Do Van (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
The study aims to establish a model analyzing factors affecting the import decisions of customers on E-commerce platforms. The study was conducted through an online interview using a structured questionnaire with 323 customers. The results indicate seven main factors affecting customers’ import decisions on E-commerce platforms including (1) Search for information online; (2) Perceived usefulness; (3) Perceived ease of use; (4) Price; (5) Trust; (6) Perceived risks; and (7) Online purchasing experience. Additionally, the result of the study also shows customers’ gender, age, matrimonial status, occupation, education, and income make no significant difference to their importing decision for goods via E-commerce.